CO2 quality control through scrubbing in oxy-fuel combustion: Simulations on the absorption rates of SO2 into droplets to identify operational pH regions. (June 2015) - Liu, Dunyu; Wall, Terry; Stanger, Rohan; Luo, Caimao
Highlights: Simulations were conducted on droplets in a spray tower. Impacts of droplet position, CO2, and droplet size were investigated. Results have implications in the controlling region and the operational pH. The operational pH of the exit liquid is established based on two criteria. The operational pH region graph is used to guide the operation of a spray tower. Abstract: Oxy-fuel combustion is a promising CCS technology which is being demonstrated prior to commercialization. While the flue gas in oxy-fuel combustion is concentrated in CO2, it contains impurities such as SO2 . The elimination of SO2 can provide a clean CO2 stream ready for storage. SO2 is commonly washed by sodium based spray towers with high efficiency but CO2 impacts are significant. A theoretical model was developed based on the two-film mass transfer model, and considering both the SO2 and CO2 reactions with sodium solutions. This model was firstly used to simulate the dynamic experimental results reported in our previous paper to confirm its applicability. With this model, simulations then were carried out on the absorption rate of SO2 into droplets with three droplet sizes: 100 μm, 500 μm and 1000 μm, one sodium concentration of 0.08 M (back calculated from liquid analysis), a range of pH from 4 to 12.5 and a range of SO2 concentrations from 19 ppm to 1500 ppm. Simulations focus on the impacts of droplet position, gas phase CO2 and droplet size on the absorption rate of SO2 . These impacts are closely related with pH values. Taking a typical pH of 7 for example, the absorption rates of SO2 for droplets close to nozzles which move relative to the gas are significantly higher than these below nozzles which are at the terminal velocities, and the differences between two positions are larger for higher concentrations of SO2 with the concentrations range from 200 ppm to 1500 ppm. CO2 has a negative impact on the absorption rate of SO2 through reducing the gas phase mass transfer coefficient of SO2 in the gas phase controlled region and also through generating more acidic conditions at the liquid phase interface. Reducing the droplet size from 500 μm to 100 μm has a more significant improvement on the absorption rate of SO2 than from 1000 μm to 500 μm. Result: have implications in the controlling region and the operational liquid pH region. The controlling region is related to the droplet position. The droplets close to nozzles are located in the mixed controlled region or the gas film controlled region; and the droplets below nozzles can be located in three regions depending on the concentration of SO2 and pH. A lower concentration of SO2 and a higher pH are favourable for the absorption rates of SO2 to be located in the gas phase controlled region. The operational pH of the exit liquid may be established based on two criteria: a reasonable absorption rate of SO2 and a sodium reagent loss as NaHCO3 . The optimal operational region is then in the region 2 where the absorption rate of SO2 is still high and reagent use is minimized. The region 2 can be further divided into four sub regions. In the region 2–1 and the region 2–2, the absorption rate is moderate, but there is too much Na + wasted for CO2 capture. In the region 2–3, there is a moderate amount of Na + wasted for CO2 capture. In the region 2–4, Na + wasted for CO2 capture is minimized, but the effective ratio of Na + is still not the maximum. The necessary operational pH region graph can be used to guide the operation of a spray tower.